The Microcephaly-Capillary Malformation Syndrome - Mirzaa, Ghayda M. (2011)
We report on three children from two families with a new pattern recognition malformation syndrome consisting of severe congenital microcephaly (MIC), intractable epilepsy including infantile spasms, and generalized capillary malformations that was first reported recently in this journal [Carter et al. (2011); Am J Med Genet A 155: 301–306]. Two of our reported patients are an affected brother and sister, suggesting this is an autosomal recessive severe congenital MIC syndrome.